Sodalite solids formation at the surface of iron oxide and its impact on flocculation - Senaputra, A.; Fawell, P.; Jones, Franca; Smith, P. (2016)
© The Minerals, Metals & Materials Society 2016. Sodalite represents the main desilication product (DSP) phase formed from reactive silica during alkaline digestion of bauxite in the Bayer Process. Previous studies into DSP effects on bauxite residue flocculation have focused on flocculant selection or digestion optimisation, not answering a fundamental question: does DSP coat the residue and thereby change surface properties? This study sought to answer that question by contrasting the physicochemical properties of hematite slurries (as a model phase for residue) containing DSP where it was either made in-situ or added as a physical mixture. On the basis of differences found in dewatering behaviour, zeta potential, desilication rates and microscopy of the solids, it is proposed that DSP nuclei initially associate with the hematite surface and subsequently affect flocculant adsorption chemistry, resulting in different extents of flocculant adsorption and smaller aggregates. The practical implications for flocculation processes are discussed.